MULTIMEDIA AS A PRONUNCIATION TEACHING TECHNIQUE IN ENGLISH LANGUAGE TEACHING - Hendrety, Yuyun (UNIVERSITAS TRIDINANTI PALEMBANG, 2017)
ABSTRACT: Second language educators realize the importance of teaching pronunciaation skills explicitly, but they still do not give much attention in their methodologies. They are not reluctant to teach pronunciation skills, but they do not know the best methods for helping students achieve adequate pronunciation skills. The main ideas of pronunciation teaching are twofold: to develop intelligible speech and to be able to effectively communicate in the target language. The main goal of this paper is to suggest possible benefits for English learners realized for multimedia teaching technique for pronunciations skills.Â Key words: multimedia, pronunciation, English language teaching